2006
DOI: 10.1080/07373930500538899
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Scale Pneumatic Conveying Dryer of Rough Rice

Abstract: This article studies the possibility of reducing the high initial moisture content of wet rough rice using a small-scale low-cost pneumatic conveying dryer as a first stage dryer. The parameters investigated are final moisture content, surface temperature of rough rice, head rice yield, drying rate, power consumption per unit mass of evaporated water, and physical characteristics of rice. Parametric effects of the following variables are examined: velocity of drying air from 20 to 30 m/s, feed rate of rough ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[1,[4][5][6] Kaensup et al, [1] for example, investigated the use of pneumatic drying for paddy and found that the moisture content of paddy could be rapidly decreased, especially at a higher inlet air temperature. Nevertheless, pneumatic drying suffers from some drawbacks; in particular, in terms of excessive cracks and discoloration of dried paddy kernels.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1,[4][5][6] Kaensup et al, [1] for example, investigated the use of pneumatic drying for paddy and found that the moisture content of paddy could be rapidly decreased, especially at a higher inlet air temperature. Nevertheless, pneumatic drying suffers from some drawbacks; in particular, in terms of excessive cracks and discoloration of dried paddy kernels.…”
Section: Introductionmentioning
confidence: 98%
“…Paddy may be dried in two stages; the first stage involves fast drying, while drying in the second stage must be slower to avoid excessive kernel breakage. Many drying techniques can be used for first-stage drying, including pneumatic drying, [1] fluidized bed drying, [2] and superheated-steam fluidized bed drying. [3] Ambient air ventilation may be used to dry paddy in the second stage.…”
Section: Introductionmentioning
confidence: 99%
“…because of its simplicity in construction, efficiency in terms of operations, and environmental and economical aspects as compared to other conveying and drying units. 9,11,14 The drying operation in these units is characterized by a coherent flow of a preheated gas−grain mix, in which grains are dehydrated or dried by the preheated air during transportation through the air duct, and thereafter the grains are separated according to size by some cyclone systems. There has been enormous research work in the broad area of pneumatic conveying and powder technology.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of pneumatic conveying and drying systems are wide in various industries, such as for pulverized coal and ash handling in power plants, , sawdust for pellet production, calcinations of gypsum, , cement production, , and food and pharmaceutical product processing. , Especially in the food industries, pneumatic conveying and drying has become very popular for batch production or the processing of agro-based food products such as wheat, corn, turmeric, tea, and coffee etc. because of its simplicity in construction, efficiency in terms of operations, and environmental and economical aspects as compared to other conveying and drying units. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation